Characteristics of Fracture Propagation Induced by Supercritical CO2 in Inter-Salt-Shale Reservoir. (10th April 2019) - Zhang, Yixiang; He, Jianming; Li, Fengxia; Fan, Xin; Li, Xiao
Abstract : Hydraulic fracturing using freshwater is difficult for the commercial exploitation of a shale oil reservoir in Jianghan Basin with a continental saline lake basin sedimentary background. Supercritical CO2 (SC-CO2 ) is a promising fracturing fluid under consideration for the reservoir stimulation, especially in the case of the presence of water sensible salt layers. In this study, SC-CO2 fracturing experiments on the inter-salt-shale and salt specimens, which were obtained from the drilling well, were carried out in the laboratory. The characteristics of fracture propagation, including morphology and width variation, were analyzed based on the observations of a stereoscopic microscope, X-ray micro-CT scanner, and 3D scanner. The existing weak planes in the shale can really impact the fracture propagation in SC-CO2 fracturing. Deflection, branching, and approaching can occur during the process of fracture propagation. The average width value of the reactivated natural fracture is bigger than that of a newly created fracture. In addition, the fracturing results indicate the greater breakdown pressure of rock salt if compared with the inter-salt-shale. The induced fractures in the salt specimen are compact and smaller in average width than those in the shale specimen. The higher breakdown pressure and relatively smaller fracture width of rock salt are real challenges for the fracturing of an inter-salt-shale oil reservoir.